2023
DOI: 10.3389/fmed.2023.1152077
|View full text |Cite
|
Sign up to set email alerts
|

FindMyApps eHealth intervention improves quality, not quantity, of home tablet use by people with dementia

David P. Neal,
Leanne Kuiper,
Daniela Pistone
et al.

Abstract: IntroductionFindMyApps is a tablet-based eHealth intervention, designed to improve social health in people with mild dementia or mild cognitive impairment.MethodsFindMyApps has been subject to a randomized controlled trial (RCT), Netherlands Trial Register NL8157. Following UK Medical Research Council guidance, a mixed methods process evaluation was conducted. The goal was to investigate the quantity and quality of tablet use during the RCT, and which context, implementation, and mechanisms of impact (usabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Detailed observations regarding use of the tablet and FindMyApps app have been reported elsewhere. 11 Adherence rates to the advised training scheme were 66.7% in the experimental arm and 64.5% in the control arm (n tot = 122, chi-squared = 0.06, p = 0.80). No harms associated with the interventions were identified.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…Detailed observations regarding use of the tablet and FindMyApps app have been reported elsewhere. 11 Adherence rates to the advised training scheme were 66.7% in the experimental arm and 64.5% in the control arm (n tot = 122, chi-squared = 0.06, p = 0.80). No harms associated with the interventions were identified.…”
Section: Resultsmentioning
confidence: 94%
“…Another reason that no effects on a group level were found may be because FindMyApps appeared primarily associated with higher quality tablet interactions but not quantitatively more tablet use or adoption. 11 Many factors can limit technology adoption by people with dementia, including lack of perceived need for a device, or unwillingness or inability to invest time in learning technology. 5 , 7 , 11 Adherence rates in this study were similar in both arms (about 65%) and higher than the 56% average reported for eHealth interventions for non-communicable disease management.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations